Investment attractiveness of the region’s development pole: methodology and analysis - M. M. Avezova; A. A. Urunov; M. A. Nasimova (Управление)
The aim of the study is to develop scientiﬁc and methodological provisions for assessing the investment attractiveness of the region’s development poles and their approbation on the materials of the Sughd region of the Republic of Tajikistan. At the same time, a methodology should be developed for determining and justifying the capital investment objects with the highest return of the region’s development pole and growth point. The main objective of the research paper is to assess the investment attractiveness of the development poles as objects that most eﬀectively use the region’s limited resources. The research methods are based on the principles of system-complex, deterministic and causal approaches in combination with the principle of dynamism. In relation to the Tajik regions considered as quasi-economy, the following range of indicators has been substantiated and proposed: the region’s enterprises production total proﬁtability; market conditions (the industry production volumes dynamics and the development poles); competitive situation (the large competitors number in the region); the ratio of proﬁtable and unproﬁtable enterprises; average labour productivity; the growth locomotives presence in the region. Based on the accounting and analysis of these indicators, a comparative assessment of the investment attractiveness of the North Development Pole and the food industry of the Sughd region of the Republic of Tajikistan has been carried out. It has been proved that the investment attractiveness of the development pole is 2.3 times higher than the investment attractiveness of the food industry chosen as a base for comparison. The results of the study can be used in the regional investment policy development processes and state regulation of spatial development.